Ultrasound-Guided Proximal and Distal Suprascapular Nerve Blocks: A Comparative Cadaveric Study. Issue 6 (24th July 2019) - Blasco, Laurent; Laumonerie, Pierre; Tibbo, Meagan; Fernandes, Olivier; Minville, Vincent; Lopez, Raphael; Mansat, Pierre; Ferre, Fabrice
Abstract: Objectives: The primary aim of our study was to evaluate and compare the accuracy of ultrasound (US)-guided distal suprascapular nerve (dSSN) and proximal SSN (pSSN) blocks. Secondary aims were to compare the phrenic nerve involvement between groups and to describe the anatomical features of the sensory branches of the dSSN. Methods: pSSN and dSSN blocks were performed in 14 cadavers (28 shoulders). Ten mL of 0.2% ropivacaine colored with methylene blue was injected under US guidance. Accuracy was determined using SSN staining and the distance between predefined anatomical landmarks and the targeted SSN. The phrenic nerve (PN) was judged to be colored or not. The distribution of the sensory branches that originate from the 14 dSSNs is described. Quantitative data are expressed as median (range). Results: The pSSN was dyed more frequently than the dSSN (13 vs 11, P  = 0.59). The targeted SSN was close to the suprascapular notch (1.3 [0–5.2] cm) and the origin of the SSN (1.4 [0.2–4.5] cm) for dSSN and pSSN blocks, respectively ( P  = 0.62). For dSSN blocks, the most frequent injection site was the supraspinous fossa. Three PNs were marked in pSSN blocks, compared with none in dSSN blocks ( P  = 0.22). Three sensory branches were identified for all 14 dSSNs: the medial subacromial branch, the lateral subacromial branch, and the posterior glenohumeral branch. Conclusions: US-guided pSSN and dSSN blocks can be realized with accuracy. A distal approach to the SSN could be an alternative to interscalene brachial plexus block for the management of postoperative pain after shoulder surgery in high–respiratory risk patients.